Penyuluhan Peran Fisioterapi pada Nyeri Bahu di Poslansia Welas Asih Mojosongo - Ulfa Kumala; Wahyu Tri Sudaryanto (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Physiological and morphological changes are something that the elderly will experience due to changes in the musculoskeletal system. Degenerative conditions in the elderly include the emergence of Musculoskeletal Disorder (DMD), one of the DMDs in the elderly is shoulder pain or frozen shoulder. The role of physiotherapy in this case can include promotive, rehabilitative, curative and preventive. Physiotherapy can play a role in providing interventions in the form of modalities or exercise therapy. The method uses counseling using leaflets and lectures as well as demonstrations regarding shoulder pain in the Mojosongo compassionate elderly postal service. The evaluation is carried out by pre-test and post-test filling out a questionnaire containing 10 questions. The aim of this counseling is to increase the knowledge and understanding of elderly people regarding the meaning, signs and symptoms, treatment and exercises that can be done at home regarding shoulder pain. The results obtained were an increase in understanding regarding shoulder pain which was seen from the evaluation results, there was a significant improvement.